Proposition of an energy density topology change method for plural eigen frequencies control - Toshie SASAKI; Ichiro HAGIWARA (Nihon Kikai Gakkai ronbunshu, 2023)
It has not been solved that the fruits and vegetables such as strawberries, cells, blood and a bottle of sake are damaged, broken during transportation. It is the greatest factor in this situation that there is a dangerous vibration frequency range where these are easy to scratch and are prone to death. If there are eigen frequencies within this dangerous frequency range，it is good to be redesigned such that the eigen frequencies within this dangerous frequency range are moved out of the range. But it is difficult to apply the existing topology optimization methods using homogenization method or density method or thickness distribution method. As fundamental research, it is demonstrated the effectiveness of the proposed method based on the strain and kinetic energy density distributions of the targeted eigen modes for a flat plate compared to the conventional topology optimization method using thickness distribution as follows. (1) It is possible to control plural eigen frequencies by deciding interactively how the topology should be changed from the observation of kinetic and strain energy density distributions of the targeted eigen modes in a very short time compared to the conventional topology optimization method. (2) In the case of the proposed method, it is not necessary to get a new topology from the thickness or density distribution after the optimization results. (3) It can be checked the validity of the task set for the conventional topology optimization method by observing the strain and kinetic energy density distributions of the targeted eigen modes which are actively used in the proposed method.